IMPLEMENTATION OF DIGITAL MEDIA IN PHYSICAL EDUCATION SUPERVISION: THE CHALLENGE OF PHYSICAL EDUCATION SUPERVISION IN INDUSTRIAL REVOLUTION 4.0 (Practitioner Research, 2019)
This paper discusses the importance of digital media for conducting physical education supervision. The coming of twenty first century in which digital media colors the education suggests that the education supervision should be shifted from the old to the new paradigm. Digital media in physical education supervision such as using Facebook and WhatsApp is a very important innovation in the dynamics of education for answering the challenges of industrial revolution 4.0. Through multimedia technology, the task of physical education supervisors in carrying out their duties are maximized.